2003
DOI: 10.1111/j.1749-6632.2003.tb03213.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Involution and the Acute Phase Response

Abstract: After their roles in reproduction are completed, the mass of the uterus and the mammary gland decrease rapidly by the process of involution that involves an ordered series of events including apoptosis, neutrophil entry, the release of degradative enzymes, and phagocytosis of cellular debris. The acute phase proteins are produced by the liver and other tissues in response to inflammation or a toxic challenge. Uterocalin (SIP24/24p3) is one of these proteins. During involution, the mammary gland and uterus expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
50
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 67 publications
2
50
0
2
Order By: Relevance
“…To date, there has been only speculation about the role lipocalin 2 might play in this process. One hypothesis is that, because lipocalin 2 expression coincides with a high degree of apoptosis in an involuting tissue, lipocalin 2 may promote the cell death of invading neutrophils and thus delay neutrophil entry into a tissue until the second phase of involution (9). A proapoptotic function for lipocalin 2 has also been reported by Devireddy et al (10).…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…To date, there has been only speculation about the role lipocalin 2 might play in this process. One hypothesis is that, because lipocalin 2 expression coincides with a high degree of apoptosis in an involuting tissue, lipocalin 2 may promote the cell death of invading neutrophils and thus delay neutrophil entry into a tissue until the second phase of involution (9). A proapoptotic function for lipocalin 2 has also been reported by Devireddy et al (10).…”
mentioning
confidence: 79%
“…For instance, several lipocalins (including apolipoprotein D, quiescence-specific protein, purpurin, and ␣ 1 -microglobulin) have been implicated in the modulation of cell growth and metabolism, whereas others (␣ 1 -microglobulin, glycodelin, and lipocalin 2) appear to regulate the immune response (3)(4)(5)(6). Lipocalin 2 was originally described as an acute-phase protein in the liver (7) but is also up-regulated after LPS stimulation in macrophages (8) and in the lungs of LPS-treated mice (9). In addition, lipocalin 2 may be involved in tissue involution, a highly organized process of tissue restructuring.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…24p3 was originally identified as an acute phase response gene induced in the liver, mainly by inflammatory stimuli such as TNF␣ and lipopolysaccharide (20,21). Diverse activities have been ascribed to 24p3, including roles in apoptosis, tissue involution, and ischemia-reperfusion injury (22)(23)(24). However, the most convincing function of 24p3 is its role in innate immune defense via iron sequestration.…”
mentioning
confidence: 99%
“…Lcn2 has been shown to mediate several biological processes, including mammary gland involution, induction of apoptosis, and delivery of iron (12,(17)(18)(19). In addition, structural studies have demonstrated that Lcn2 binds to enterobactin-type bacterial siderophores, which facilitate iron uptake by bacteria (16).…”
mentioning
confidence: 99%